KEPENTINGAN AMERIKA SERIKAT DALAM PROYEK IFACS (INDONESIA FOREST AND CLIMATE SUPPORT) MELALUI PROGRAM USAID (UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT) DI INDONESIA - Lisa Aulia; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this research is to know The United States‟ interest in IFACS project through USAID program in Indonesia. The project is a cooperative program between the United States an Indonesia to reduce deforestation, greenhouse gas emissions and to support the adaptation of climate change. The project takes place in Aceh, West Kalimantan, Cebtral Kalimantanan and Papua from 2010-2015. The implementation of the project involves the central government, the provincial government, the regional government, non-governmental organization, local people and private sector.The research uses qualitative methode with descriptive analysis model. Most of the data are collected through literature reviews and website searches. Then the obtained data are analyzed with theoretical approaches related to International Relations and International Cooperation. The researcher use liberalism perspective which believes that people will cooperate each other or work together to achieve the same interest. Level of analyisis is nation state with cooperation theory and national interest concept.The result of the research indicates that there are the United States‟ interest through the help that it gave for Indonesia. The interest are economy and political interest, such as securing the continuity of activities of The United States‟ companies in Indonesia.Keywords:United States, Indonesia, National Interest, USAID, IFACS